Edukacja językowa w Polsce: stan, wyzwania i perspektywy rozwoju. Część I: Nauczanie języków mniejszości narodowych i etnicznych, języka regionalnego oraz języków obcych - Banasiak, Ilona; Olpińska-Szkiełko, Magdalena; Patera, Mateusz (Neofilolog, 2025)
This report analyses the current state, challenges, and future prospects of language education in Poland. It presents statistical data on the teaching of national and ethnic minority languages, the regional language, and foreign languages, as well as an assessment of its effectiveness. Although language education in Poland aligns with EU recommendations, its outcomes require improvement. The 2021 Census shows that over 1.7 million people in Poland use a language other than Polish at home, yet minority and regional language education attracts relatively few students. English dominates foreign language learning, with nearly all students studying it as the compulsory subject. Despite extensive instruction, proficiency in English and other foreign languages remains low, as indicated by exam results. As an EU member state, Poland is committed to enhancing the effectiveness of language education. The report emphasises the need for innovative approaches to improve language acquisition and promote overall linguistic diversity in Poland.